Antiviral Effect of Oral Administration of Tenofovir Disoproxil Fumarate in Woodchucks with Chronic Woodchuck Hepatitis Virus Infection - Menne, Stephan (American Society for Microbiology, 2005)
Tenofovir disoproxil fumarate (TDF) is a nucleotide analogue approved for treatment of human immunodeficiency virus (HIV) infection. TDF also has been shown in vitro to inhibit replication of wild-type hepatitis B virus (HBV) and lamivudine-resistant HBV mutants and to inhibit lamivudine-resistant HBV in patients and HBV in patients coinfected with the HIV. Data on the in vivo efficacy of TDF against wild-type virus in non-HIV-coinfected or lamivudine-naïve chronic HBV-infected patients are lacking in the published literature. The antiviral effect of oral administration of TDF against chronic woodchuck hepatitis virus (WHV) infection, an established and predictive animal model for antiviral therapy, was evaluated in a placebo-controlled, dose-ranging study (doses, 0.5 to 15.0 mg/kg of body weight/day). Four weeks of once-daily treatment with TDF doses of 0.5, 1.5, or 5.0 mg/kg/day reduced serum WHV viremia significantly (0.2 to 1.5 log reduction from pretreatment level). No effects on the levels of anti-WHV core and anti-WHV surface antibodies in serum or on the concentrations of WHV RNA or WHV antigens in the liver of treated woodchucks were observed. Individual TDF-treated woodchucks demonstrated transient declines in WHV surface antigen serum antigenemia and, characteristically, these woodchucks also had transient declines in serum WHV viremia, intrahepatic WHV replication, and hepatic expression of WHV antigens. No evidence of toxicity was observed in any of the TDF-treated woodchucks. Following drug withdrawal there was prompt recrudescence of WHV viremia to pretreatment levels. It was concluded that oral administration of TDF for 4 weeks was safe and effective in the woodchuck model of chronic HBV infection.